Telehealth experiences of vulnerable clients living in Tasmania. (25th January 2022) - Van Dam, Pieter Jan; Caney, Diane; Turner, Richard C.; Griffin, Phoebe; Dwyer, Mitchell; Prior, Sarah
Abstract: Objective: To understand the experiences of vulnerable clients who used telehealth during the Coronavirus pandemic. Design: The study employed a qualitative enquiry, utilising semi‐structured interviews lasting 30‐60 minutes with a thematic analysis approach to explore factors influencing client experience with telehealth. Setting: A wide range of locations across Tasmania, Australia. Participants: Twelve participants who were considered to be vulnerable on a number of domains, including: health and human wellbeing factors, social risk factors, functional limitations, and individual behavioural factors. Interventions: The provision of telehealth consultations to vulnerable clients. Main outcome measures: Four global themes were discovered: i) Telehealth saves time, money and energy; ii) User friendly technology facilitates care; iii) Rapport and confidentiality helps clients to feel safe; and iv) Fit for purpose telehealth provides a quality service. Results: The discovered themes entailed the major finding that most participants were satisfied with the overall quality of the telehealth service they received and the convenience of this service. Concerns were raised regarding the limitations around social interaction, physical examination, and access to fit‐for‐purpose telehealth devices. Conclusion: This research with vulnerable clients, from Tasmania, supports the evidence that the utilisation of telehealth allows more convenient access to care. To optimise the service, however, concerns regarding the desire for social interaction, appropriate physical examination, and access to fit‐for‐purpose telehealth devices will need to be addressed.